What Information Do Teenagers with Idiopathic Scoliosis and Their Families Need When First Diagnosed? - Çolak, Tuğba Kuru; Akçay, Burçin; APTİ, ADNAN; Çolak, İlker; Bettany-Saltikov, Josette (Erkan Mor, 2021)
Objective: The aim of this study was to determine the information needs of individuals with adolescent idiopathic scoliosis (AIS) and theirfamilies when the disease was first diagnosed.Materials and Methods: A total of 117 patients with AIS and their parents volunteered to participate in this study. A survey developed specificallyto assess the information needs of AIS patients and their families was sent by e-mail. Of the AIS patients, 59.8% were aged >16 years andcompleted the survey alone, and 40.2% were aged <16 years and they completed the survey together with their parents.Results: The results of this study demonstrated that in the initial diagnosis, scoliosis could be observed even if the angle was <20°. Generally,scoliosis was first noticed by the child’s mother. As expected, at the time of the initial diagnosis, the children diagnosed as having scoliosis wereupset and confused and their parents also felt upset and worried. The information most needed was reported to be answers to the questions of“Will it get better, what are the causes of scoliosis?”, “What is scoliosis and what are the possible treatment options?”, and the least frequentlyasked question was “Will surgery be needed?”.Conclusion: Clear, accurate, complete, and personalized information is required by patients and their families. This information is essential inenabling patients to make major decisions and to take ownership and responsibility for the decision. Involvement in decision-making helps toimprove compliance with treatment and finally also improves satisfaction with the agreed treatment method used.
Keywords: Adolescent Idiopathic Scoliosis; Survey; Information Needs; Family